Casos de Ensino em Administração: Dona Flor: Desintermediar ou ser Desintermediada! - Aline Stange; Carolina de Arantes Montagna; Victor Manoel Cunha de Almeida (RAC: Revista de Administração Contemporânea, 2012)
The Dona Flor teaching case portrays the moment in which Pedro Brasil, founder of an erotic product reseller for women through direct sales, was looking for ways to keep his business healthy and growing. One possibility was derived from the fact that consumers did not recognize specific brands ofproducts, since there were no large companies in the erotic products market. The channel structure of the company, however, hindered the exploitation of this opportunity. The case highlights the fragilityof the company’s relationship with suppliers and with catalog distributors. Students should therefore consider the disintermediation of both upstream and downstream links in the value chain and the implications of this decision for the business. Moreover, the case suggests the possibility that Dona Flor itself was in danger of being disintermediated, requiring the evaluation of strategies to mitigate this risk, which include the development of a private label. The goal is to enable students to sketch the path-to-market diagram, and, based on it, provide alternatives for the company, considering the advantages and disadvantages of each proposal. They should also realize the importance of the differential offered by Dona Flor and the limitations it imposes on the exploitation of different distribution channels.